The Effect of Lifestyle, Cafe Atmosphere, and Word of Mouth on Coffee Shop Purchasing Decisions in Yogyakarta City - Septiono, Muhammat Imadudin; Sofiati, Sofiati (LifeSciFi, 2026)
The booming coffee industry in Yogyakarta, home to 41 campuses, has driven the opening of 533 coffee shops in strategic locations, making them lifestyle hubs, social spaces, and productivity centers for students and the urban community. This study aims to determine whether lifestyle, cafe atmosphere, and word of mouth influence purchasing decisions in choosing a coffee shop in Yogyakarta. This study used a quantitative associative-causal survey with 130 coffee shop consumers in Yogyakarta, sampled via convenience sampling. Data were collected online through a 1–5 Likert questionnaire and analyzed in SPSS 27 using validity/reliability tests, classical assumption checks, t-tests, F-tests, R², and multiple linear regression. The results showed that lifestyle significantly influenced purchasing decisions, but the cafe atmosphere had a negative and significant effect on purchasing decisions, and word of mouth was proven to significantly influence purchasing decisions. Simultaneously, the variables of lifestyle, cafe atmosphere, and word of mouth significantly influence purchasing decisions. These results indicate that lifestyle, cafe atmosphere, and word of mouth, if managed properly, will increase purchasing decisions in all coffee shops in the city of Yogyakarta.